PENGEMBANGAN PERANGKAT PEMBELAJARAN IPA TERPADU PADA MATERI ENERGI UNTUK SISWA KELAS VII MADRASAH TSANAWIYAH NEGERI 1 KOTA GORONTALO - Mastin M Gubali; Yoseph Paramata; Fitryane Lihawa (Jambura Physics Journal, 2021)
The purpose and implementation of this research were to produce the development of class VII integrated science learning tools for students of MTsN. 1 Gorontalo’s City dan to determine their effectiveness. The method in this research was used the Research and Development (R and D) approach. The step in the research was used the ADDIE models, where the development processes are: Analysis, Design, Development, Implementation, and Evaluation. The results were showed that interpretation of the average assessment of the learning tools (syllabus learning, RPP, LKPD, teaching materials, learning media, and learning outcomes test) was very appropriate. Where the validation index of all of the items was ranged from 0.75 – 0.95. The conclusion was valid by calculating the consistency of the panelists’ assessment, where the reliability was 0.77 – 0.95. the results of observer’s observation (1 and 2) on the implementation of learning as from using of learning tools in the average percentage was obtained 92,35%.  There was a significant increase in student outcomes at the pretest and posttest. This increase was included in the category (g-high). Thus the development of integrated science learning tools in energy materials for class VII students was meet requirements that were valid and reliable, feasible, and effective for improving student learning outcomes.